The evolution of digital learning in higher education - Hashim, Hazwati (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The past two decades have witnessed a revolution in higher learning in the form of digital learning. What began as basic online resources and course materials has soon evolved into an interactive, technology-driven model that serves virtual classrooms, interactive spaces, and individualised learning environments. As institutions adapt to the demands of a digital age, the integration of technology in teaching and learning continues to transform the delivery and availability of knowledge. Higher education has been deeply influenced by digital learning, which has opened the door to new, effective methods of teaching and learning that extend beyond classroom walls. With the integration of various online tools, students can now engage with content, collaborate with peers, and receive instruction from anywhere in the world. This shift has expanded educational opportunities, allowing for a diverse range of learners, from working professionals to international students, to pursue academic goals without the constraints of physical classroom settings.